The Effect of Community Based Non-Communicable Disease Services on the Quality of Life of People Living with HIV in Uganda: A Randomized Controlled Trial - Ddamulira, Christopher; Nsereko, Norman; Musoke, Miph (Direct Research Journal of Public Health and Environmental Technology, 2020)
A comprehensive and culturally applicable community based Non Communicable Diseases (NCD) services package was implemented with an aim to test the effectiveness of the community based NCD services that integrate HIV and Non-Communicable Diseases in communities to improve the quality of life (QoL) of people with HIV living with NCDs in Uganda. The Randomized Controlled Trial (RCT) was conducted to compare the efficacy of the community based NCD services as intervention. The control group received the usual HIV services in the community by the HIV expert clients in Uganda. Participants were randomly allocated to receive weekly and monthly intervention sessions by village health teams (VHTs), expert clients and community volunteers or standard care in the community ARV drug distribution points. Independent t-tests were performed to compare changes in the QoL scores at the baseline and the endline. The effect of the intervention on the QoL was tested using Pearson correlation and linear regression analysis. Between November and December 2018, 1076 individuals were screened, of whom 438 were randomly assigned to either the intervention or control group in the ratio of 1:1. The post intervention results revealed that the community based NCD services were effective and contributed 31.9% to the overall improved the QoL in all the three domains; the physical, environmental and social relationship domains. Therefore, designing such interventions in all community HIV drug distribution points would reduce the co-morbidities related to NCDs and HIV, and improve the overall quality of life. Furthermore, it could be useful to reduce stigma and increase their social support network. Findings could be utilized at regular community service settings for its sustainability and long-term effect. The intervention created improved understanding of HIV and NCD integration health promotion strategies and community support systems activities by the VHT, ART expert clients and the community volunteers.
Keywords: Community; Non-Communicable Diseases; Services; Quality of Life; HIV; People Living with HIV; Uganda